2021
DOI: 10.1056/nejmoa2023294
|View full text |Cite
|
Sign up to set email alerts
|

A Microbiota-Directed Food Intervention for Undernourished Children

Abstract: BACKGROUND More than 30 million children worldwide suffer from moderate acute malnutrition (MAM). Current treatments have limited effectiveness and much remains unknown about pathogenesis. Children with MAM exhibit perturbed development of their gut microbiota. METHODS Slum-dwelling Bangladeshi children, aged 12 to 18 months, with moderate acute malnutrition (n=124) received a microbiota-directed complementary food (MDCF-2) or an existing ready-to-use supplementary food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
216
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(222 citation statements)
references
References 32 publications
4
216
1
1
Order By: Relevance
“…The gut microbiota can influence the peripheral and central nervous system and host metabolism via production of neurotransmitters and short chain fatty acids [ 31 , 32 ]. A study in undernourished Bangladeshi infants at 12 to 18 months of age described changes in concentrations of blood plasma proteins linked to neurodevelopment due to manipulation of the gut microbiota [ 33 ]. Although the head growth of the infants in our trial was still inferior to the growth in utero, an increased head circumference growth rate might be associated with improved neurodevelopment of extremely preterm infants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota can influence the peripheral and central nervous system and host metabolism via production of neurotransmitters and short chain fatty acids [ 31 , 32 ]. A study in undernourished Bangladeshi infants at 12 to 18 months of age described changes in concentrations of blood plasma proteins linked to neurodevelopment due to manipulation of the gut microbiota [ 33 ]. Although the head growth of the infants in our trial was still inferior to the growth in utero, an increased head circumference growth rate might be associated with improved neurodevelopment of extremely preterm infants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes to Bacteroidetes ratio (F/B ratio) has been shown to be correlated with obesity and other diseases in human and amimal studies 48 .The observed increase of Firmicutes over Bacteroidetes at day 8 was positive in the present study is consistent with our previous study which showed a higher proportion of Firmicutes (43 ± 4; mean ± SEM %) over Bacteroidetes (33 ± 3) with healthy children in Bangladesh 42 . A recent microbiota study carried out in Bangladesh showed tremendous success in improving child health by attracting bene cial gut microbiota via microbiota directed complementary foods (MDCF) 49 . Although the MDCF alone has succeeded in increasing weight for length Z score with positive changes in the level of some plasma proteins in study children, we would propose to combine MDCF study with the CHoBI7 WASH program to improve the gut microbiota composition of young children.…”
Section: Discussionmentioning
confidence: 99%
“…A microbiota-directed complementary food prototype was developed for 12–18 m old malnourished children and been found to be beneficial for weight and height gain, increase in plasma protein levels, and population by Faecalibacterium and Bifidobacterium spp. [ 69 ].…”
Section: Intestinal Microbiome and Dietmentioning
confidence: 99%